Cryptococcal titan cells: When yeast cells are all grown up - García-Rodas, Rocío; de Oliveira, Hc [UNESP]; Trevijano-Contador, Nuria; Zaragoza, Oscar (Springer Nature, 2019)
Cryptococcus neoformans is a human pathogenic yeast that causes hundreds of thousands of deaths worldwide among susceptible individuals, in particular, HIV+ patients. This yeast has developed several adaptation mechanisms that allow replication within the host. During decades, this yeast has been well known for a very peculiar and unique structure that contributes to virulence, a complex polysaccharide capsule that surrounds the cell wall. In contrast to other fungal pathogens, such as Candida albicans or Aspergillus fumigatus, the role of morphological transitions has not been studied in the virulence of Cryptococcus neoformans since this yeast does not form hyphae during infection. However, in the last years, different groups have described the ability of this fungus to change its size during infection. In particular, Cryptococcus can form “titan cells,” which are blastoconidia of an abnormal large size. Since their discovery, there is increasing evidence that these cells contribute, not only to long-term persistence in the host, but they can also actively participate in the development of the disease. Recently, several groups have simultaneously described different media that induce the appearance of titan cells in laboratory conditions. Using these conditions, new inducing factors and signaling pathways involved in this transition have been described. In this article, we will review the main phenotypic features of these cells, factors, and transduction pathways that induce cell growth, and how titan cells contribute to the disease caused by this pathogen.
Keywords: Capsule; Cryptococcus neoformans; Morphogenesis; Titan cell; Virulence